Inhibitor of apoptosis-stimulating protein of p53 (iASPP) prevents senescence and is required for epithelial stratification. - Notari, M; Hu, Y; Koch, S; Lu, M; Ratnayaka, I; Zhong, S; Baer, C; Pagotto, A; Goldin, R; Salter, V; Candi, E; Melino, G; et al. (2011)
Inhibitor of apoptosis-stimulating protein of p53 (iASPP) is the most ancient member of the ASPP family of proteins and an evolutionarily conserved inhibitor of p53. iASPP is also a binding partner and negative regulator of p65RelA. Because p65RelA and the p53 family members often have opposite effects in controlling cell fate, it is important to understand the cellular context in which iASPP can regulate their activities. To address this question and to study the biological importance of iASPP in vivo, we generated a transgenic mouse in which iASPP expression is controlled by the Cre/loxP recombination system. We observed that iASPP is able to prevent premature cellular senescence in mouse embryonic fibroblasts. iASPP loss resulted in increased differentiation of primary keratinocytes both in vitro and in vivo. In stratified epithelia, nuclear iASPP often colocalized with p63 in the nuclei of basal keratinocytes. Consistent with this, iASPP bound p63 and inhibited the transcriptional activity of both TAp63α and ΔNp63α in vitro and influenced the expression level of p63-regulated genes such as loricrin and involucrin in vivo. In contrast, under the same conditions, p65RelA was frequently expressed as a cytoplasmic protein in the suprabasal layers of stratified epithelia and rarely colocalized with nuclear iASPP. Thus, iASPP is likely to control epithelial stratification by regulating p63's transcriptional activity, rather than p65RelA's. This study identifies iASPP as an inhibitor of senescence and a key player in controlling epithelial stratification.